Pengaruh Kompetensi Guru Terhadap Hasil Belajar Siswa Madrasah Tsanawiyah - Alamsyah, Moch. Firdaus; Darmawan, Didit (Lembaga Yasin AlSys, 2025)
This study employs a qualitative method with a literature study approach, aiming to examine the influence of learning motivation on academic achievement at the MTs (Islamic junior high school) level. The literature review encompasses theoretical studies, references, and various scientific literature relevant to values and norms within the realm of education, which serve as the research focus. The collected data are descriptive in nature, derived from various sources including articles, journals, and websites selected for their relevance to the research topic. The selection of sources is based on their academic quality and alignment with the theoretical framework employed. This research focuses on two main variables: teacher competence as the independent variable and academic achievement as the dependent variable. Data analysis is conducted descriptively and qualitatively to reveal the relationship between these two variables and to provide scientific contributions to the development of the teaching and learning process within MTs settings. Through this study, readers are expected to gain deeper insights into the factors associated with learning motivation and its impact on student outcomes, particularly at the MTs level.